The Resistance of Certain Tissues to Invasion: Penetrability of Explanted Tissues by Vascularized Mesenchyme - Eisenstein, Reuben (1973)
If puppy tissues are explanted onto the chick chorioallantoic membrane, those tissues which normally have a blood supply are rapidly invaded by vascularized mesenchyme of host origin. Hyaline cartilage, a tissue virtually devoid of blood vessels, is impenetrable by proliferating mesenchyme of the host, while calcified cartilage, which normally is vascularized, is penetrable. The stroma of the cornea, another normally avascular tissue, is readily penetrable, but Descemet's membrane forms a barrier to invasion by host tissues. The experimental system used permits the design of experiments in which the study of factors responsible for the resistance of tissues such as cartilage to invasion can be undertaken.